OUT to IN: a body-oriented intervention program to promote preschoolers’ self-regulation and relationship skills in the outdoors - Veiga, Guida; Guerreiro, Daniela; Marmeleira, José; Santos, Graça Duarte; Pomar, Clarinda (Frontiers in Psychology, 2023)
Introduction: Time for movement and outdoor experiences has decreased in children’s daily lives. Nevertheless, a growing body of research has shown that body-oriented interventions and outdoor time benefit preschoolers’ social-emotional development, a foundation for mental health. OUT to IN is a body-oriented intervention program implemented outdoors, designed to promote preschoolers’ social-emotional competence. This study aimed to evaluate the effects of OUT to IN on preschoolers’ self-regulation and relationship skills. Methods: A cluster randomized trial with multi-method and multi-informant assessment was implemented including 233 preschoolers (122 boys, Mage=5.07 years), from 4 preschools (8 groups with OUT to IN intervention, 4 groups without intervention – control group). The 153 children allocated to the OUT to IN group participated in biweekly sessions for 10 weeks. OUT to IN sessions followed a body-oriented approach comprising exercise play, relaxation, and symbolization activities, implemented outdoors by a psychomotor therapist and the preschool teacher. Sessions enabled children to feel, observe and control their bodily states and understand the relationship between their bodies and emotions. Teachers participated in a brief course and on 20 biweekly relaxation sessions. Children’s’ self-regulation was measured through specific tasks and a parent questionnaire. Relationship skills (i.e., empathy, communication, cooperation and sociability) were measured through parents’ and preschool teachers’ questionnaires. Mann–Whitney test was used to study differences at baseline between the OUT to IN group and the control group, and to study differences in the 10- week changes between both groups. Wilcoxon Test was used for intragroup comparisons. Results: After the 10-week intervention period, children who participated in OUT to IN showed significant improvements on self-regulation and relationship skills (empathy, cooperation and sociability), in comparison to the control group who did not show any significant improvements. Large size effects (η2 > .14) were found for most of the variables related to self-regulation and small (η2 > .01), medium (η2 > .06) and large size effects (η2>.14) were found for the variables related to relationship skills. Conclusion: OUT to IN showed to be an effective body-oriented intervention program in improving children’s self-regulation and relationship skills, which are recognized foundations for mental health and well-being.